The effect of plant growth promoting rhizobacteria on Datura stramonium L., Abutilon theophrasti Med., Onopordon acanthium L. and Verbascum thapsus L. seed germination - Božić, Dragana; Jovanović, Ljubinko; Raičević, Vera; Pavlović, Danijela; Sarić-Krsmanović, Marija; Vrbničanin, Sava (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2014)
The effects of several bacterial media [Bacillus licheniformis population 1 (MO1); B. licheniformis population 2 (MO2); B. subtilis (MO3); B. megatherium (MO4); humates (MO5)] on seed germination of Datura stramonium L., Abutilon theophrasti Med., Onopordon acanthium L. and Verbascum thapsus L. were tested. Seeds were germinated in Petri dishes containing solutions with different bacterial media. The highest germination percentage in all treatments was recorded for V. thapsus seeds (100.0%). Different treatments had diverse effects (stimulative or inhibitory) on seed germination of D. stramonium [from 5% (MO1) to 13.3% (MO3), with 10.0 % in H20], A. theophrasti [from 28.3% (MO3) to 65.0% (MO5), with 43.3 % in H20] and O. acanthium [from 10.0% (MO2) to 13.3% (MO1 and MO3), with 6.7% in H20], depending on the type of media and weed species.